PERANAN APARATUR YANG PROFESIONAL GUNA MEWUJUDKAN PELAYANAN PRIMA DALAM BIROKRASI - Ma’mun, Sukron (Universitas Madura, 2016)
In the development of society increasingly complex and increasingly heterogeneous society's will to get the best service in the bureaucracy, then the apparatus required to always provide a quality service, so that people are satisfied with the services provided by officials in the bureaucracy.To provide a quality service, which works in the bureaucratic apparatus, the apparatus must be professional, because only apparatus that professionals who truly understand the wishes of the people, and which is able to provide excellent service to the community. In this case, the role of the professional apparatus in order to realize the excellent service in the bureaucracy is very important, so that future bureaucracy in Indonesian become a bureaucracy that really provide the best service to the community. In this article, we try to give explanations regarding the role of the professional personnel in order to realize the excellent service in the bureaucracy, what excellent service, and although how to provide excellent service to the community.